The Impact of the Covid-19 Pandemic on the Financial Performance of Islamic Banking Listed on the Indonesia Stock Exchange (IDX) - Widya Widya; Sitti Nurbaya; Nasrullah Nasrullah; Dg. Maklassa (SEIKO : Journal of Management & Business, 2021)
Abstract This researce is a type of quantitative research with the aim of knowing the impact of the Covid-19 pandemic on the financial performance of islamic banking listed on the Indonesia Stock Exchange (IDX). The sampel in this study was taken from the financial statements of islamic banks listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic. The type of data used in this study is secondary data. The data collection technique in this research is a documentation study technique.In this study, the ratios used for measuring financial performance are the liquidity ratio represented by FDR, the profitability ratio represented by ROA, the solvancy ratio represented by CAR and the asset quality ratio represented by NPF. To analyze data, paired t-test are used as the analytical tool. The resulte showed that there were significant differences in the liquidity ratio represented by FDR, the profitability ratio represented by ROA, the asset quality ratio represented by NPF. Meanwhile, the result of the CAR ratio shows that there was significant difference before and during Covid-19. This indicates that Covid-19 has an impact on the financial performance of the islamic banks registered on the Indonesia stock exchange (IDX). Keywords: Before Covid-19, During Covid-19, Financial Performance, FDR, ROA, CAR and NPF.